BUSINESS EFFICIENCY AND BUSINESS PERFORMANCE OF COCONUT SUGAR SMES IN BANYUMAS REGENCY - Lilis Siti Badriah; Arintoko Arintoko; Dijan Rahajuni (Faculty of Economics and Business, University of Pasundan, 2021)
This study aims to analyze economic efficiency and the factors that influence the performance of coconut sugar SMEs in Cilongok District, Banyumas Regency. This study uses primary data obtained through interviews with 162 respondents. By using Benefit-Cost Ratio analysis and multiple regression, this study finds that the coconut sugar business in Cilongok District, Banyumas Regency is not yet efficient and the coconut sugar business performance is positively influenced by financial capital. While social capital and human capital do not affect it. This research implies the need for continuous efforts from all stakeholders to provide business assistance and certainty in product marketing so that product prices become more stable. In addition, it is also necessary to optimize the potential of social and human capital to strengthen the role of financial capital in improving business performance. This can be done through the institutionalization of social capital and optimizing the role of the village government in facilitating cooperation with various parties.